Webs and plots between politics and media in the fight against corruption in Brazil: the Lava Jato case - Carlos Renan Moreira Bretas; Maria Alice Nunes Costa (Intexto)
This article proposes an interdisciplinary study of Sociology, Political Science, Law and Social Communication, analyzing how was the relationship between media, politics and Justice in Brazilian fight against corruption during the Lava Jato operation (2014-2021). Our goal is to discuss how media contributed to construct and deconstruct corruption narratives, influencing the public opinion and the political field. We applied a descriptive and analytical method that comprises data collection and literature review. The results found indicate that media was the main tool for disseminating the operation’s results, inserting the authorities responsible for the investigations and sentences in legal proceedings into the political scenario. The leading role assumed by public agents and institutions through media was able to direct public opinion against the politicians involved, influencing the outcome of the 2018 elections. On the other hand, in the context of dissemination of political media scandals, the wide media coverage of the corruption scandals investigated by Lava Jato operation was responsible for overshadowing society’s perception of other problems in the country, in a similar way to what occurred in other countries.